UTILIZING GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS - Kurniawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the 2013 curriculum aiming to actualize science learning not only as a conceptual understanding but also as a process to train students' skills, in this case, science process skills. This research was a classroom action research conducted in September 2019 with 31 students of grade VII.1 SMP Negeri in Teluk Kuantan. The instruments were the observation sheet and the student response questionnaire to the inquiry learning model. The results showed that the students’ science process skills in cycle I were 64.69 with sufficient criteria, and in cycle II it was 71.22 with good criteria. Students’ responses to the learning were positive, in which students strongly agreed with learning because it improved students' science process skills. The conclusion based on the results of the research was that the guided inquiry learning model improved students' science process skills and elicited a positive response from grade VII.1 students at SMP Negeri 1 Teluk Kuantan.